A dynamic current hysteresis model for IGZO-TFT. (November 2022) - Li, Yu; Huang, Xiaoqing; Liao, Congwei; Wang, Runsheng; Zhang, Shengdong; Zhang, Lining; Huang, Ru
Highlights: Dynamic current hysteresis that can well capture the effect of the trap energy level, trap density and scan rate is proposed. This Dynamic current hysteresis model based on trap kinetics is well compatible with SPICE simulations. The methodology of this hysteresis model can be well extended to other trap kinetics theory and emerging devices. Abstract: This paper proposes a dynamic current hysteresis model for the Indium Gallium Zinc Oxide Thin Film Transistor (IGZO-TFT). Based on the Shockley-Read-Hall (SRH) theory, a kinetic equation that accurately describes the interface trap's capture/emission behaviour is presented, which can incorporate the effect of interface trap density, trap energy level and scan rate dependency. Further, the kinetic equation is solved using a sub-circuit approach, combined with a calibrated TFT static current model, to achieve an accurate simulation of the current hysteresis of IGZO-TFT. This model has been validated with numerical TCAD simulations and has been shown to precisely reflect the effect of trap energy level, trap density and scan rate on the current hysteresis characteristics.